PENGARUH DUKUNGAN ORANG TUA TERHADAP PEMBENTUKAN KARAKTER PANCASILA SISWA STUDY KASUS KELAS 11 SOSHUM 2 MAS AL FATTAHIYYAH TULUNGAGUNG - Mohammad Rofiqun Nizar; Mohammad Hasib; Bachrul Ulum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The formation of Pancasila character is one of the important goals in education to create students who possess religious values, mutual cooperation, independence, critical thinking, creativity, and global diversity. The success of this character formation is influenced not only by the school environment, but also by parental support as the child's first educational environment. This study aims to describe the forms of parental support in the formation of students' Pancasila character and identify the obstacles faced by parents and the madrasah administration in supporting this process at MAS Al Fattahiyyah Tulungagung. This research used a qualitative approach with a case study approach. Data were obtained through observation, interviews, and documentation. The research informants consisted of the Madrasah Principal, the Vice Principal for Student Affairs, teachers, guardians, and 11th-grade Social Sciences 2 students at MAS Al Fattahiyyah Tulungagung. Data analysis was conducted using the Miles, Huberman, and Saldana model, which included data condensation, data presentation, and conclusion drawing. Data validity was tested through triangulation of sources, techniques, and time. The results indicate that parental support in the formation of students' Pancasila character is manifested through emotional support in the form of attention, motivation, and advice; instrumental support in the form of meeting educational needs; informational support in the form of direction and guidance related to moral and religious values; and support in the form of appreciation for student effort and achievement. This support contributes to fostering religious attitudes, responsibility, discipline, mutual cooperation, and social awareness in students. Obstacles found include limited parental time due to work, less than optimal communication between parents and the madrasah, and the influence of the student's social environment. To overcome these obstacles, continuous synergy is needed between parents and the madrasah through increased communication, supervision, and character development together. Based on the results of the study, it can be concluded that parental support has a very important role in the formation of students' Pancasila character.